Strategies of Interaction between Parents and Preschool Children and Features of Ideas about Parenting - T.P. Avdulova; T.V. Krotova; G.R. Khuzeeva (Психолого-педагогические исследования)
This article reveals the problem of the relationship between the strategies of interaction of parents with preschool children and ideas about parenting in the context of studying the phenomenon of conscious parenting. Conscious and responsible parenting is considered as a transformation of the activity of education in line with higher mental functions modeled by society. Strategies of interaction of parents with a child reflect, to a greater extent, the behavioral component, while various ideas about parenting reflect, to a greater extent, the cognitive and emotional component of conscious and responsible parenting. The results showed that in the structure of strategies of interaction with a child, parents prefer explanatory and coping strategies. That is, in the parental subculture, these types of interaction are considered the most approved and acceptable in raising children. These strategies are directly correlated with such ideas about their parenting as the breadth of the value sphere in the field of raising children, acceptance of their own parenting, a positive attitude to the main institutions of socialization of the child and a high level of awareness of the age characteristics of the child. The variability of individual interaction strategies is determined by the nature of the connection between different interaction strategies. The results of the study allow us to develop technologies for educating and supporting parents. Diagnostic methods can be used as a tool for forming the metacognitive component of parenting, enhancing awareness of various aspects of the child's socialization.